Pengaruh Pemberian Ekstrak Daun Kencur (Kaempferia galanga L.) Subang terhadap Morfometrik Ayam Broiler di Daerah Tropis - Suriansyah Suriansyah Suriansyah; Andi Citra Septaningsih; Marsudi Marsudi; Adryani Ris; Sudirman Sudirman; Kasmiati Kasmiati; Putri Ramdaniah; Korbinianus Feribertus Rinca (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2026)
This study evaluated the effect of Kaempferia galanga L. (kencur) leaf extract supplementation via drinking water on morphometric traits of broiler chickens reared under tropical conditions. A completely randomized design (CRD) was applied with four treatments: P0 (0%), P1 (1% v/v; 10 mL/L), P2 (2% v/v; 20 mL/L), and P3 (3% v/v; 30 mL/L). Broilers were reared in a closed-house system until 35 days of age, and morphometric measurements included body weight, comb height, shank length, tibia length, femur length, and pelvic-related distances. Results indicated that supplementation significantly improved growth-related morphometrics, with the most consistent improvements observed at P2 (2%). The response tended to plateau or slightly decrease at P3 (3%), suggesting an optimum dose range. These findings support the potential use of kencur leaf extract as a phytogenic supplement administered through drinking water to enhance broiler growth and